Apostasy (Irtidâd) in Islamic Jurisprudence; is it a Creedal or a Political Crime: Ibn al-Humam (d. 861/1457) - Kahveci, Niyazi (Journal of History Culture and Art Research, 2017)
This article aimed to explore the nature of the penalty of the apostasy (irtidâd) to what extent it is creedal or political crime, with particular reference to Hanafite penal law which served as the law of Islamic world for a period of a millennium. In expounding this law I have chosen the text of jurist-author of this School, Ibn al-Humâm (d. 861/1457) which offered a mere document for the subject-matter. The analysis in this essay exposed that Hanafi juristic conception considered the act of apostasy not a creedal but a political offence. Thereof the ratio legis (‘illa) of death penalty imposed to the apostate (murtad) is not his commitment of disbelief (kufr) but his renouncement of the social, legal and political authority and system of the state and abandoning his membership of Muslim community after once accepted it. Consequently he has been accounted as a potential threat as a warring enemy to the survival of the Muslim community and its state. I understand that the jurists did not give the state legal authority to interrogate and punish the disbelief of its subjects. Belief of the individual rests between him and God.